A Longitudinal Study to Identify the Psychological Needs Profile of Users of Social Media in the pre-COVID and post-COVID Eras - Kakar, Ashish (Journal of the Southern Association for Information Systems, 2022)
Social media has had a huge impact on how we live and interact as a society. Yet, research literature is sparse on the psychology of users who participate enthusiastically in the social media. In this exploratory study with 222 student users we apply the theory of fundamental human needs to predict and assess the psychological profile of users who actively engage in social media. Overall the finding of the study support our hypothesis but with a few unexpected findings. Need of relationship, self-esteem and popularity-influence were found to positively impact the behavioral intention, frequency and time users spent on social media. The findings have useful practical implications for product/ project managers in understanding what motivates users to engage in social media and how social media can be designed to further enhance user participation.